Experimental Study and Numerical Simulation on Mechanical Properties of the Bottom Plate in the Assembled Composite Slab with Additional Steel Trusses - Xiuying Yang; Yuzhuo Wang; Yongxin Liu; Zhenyu Wei (Advances in Civil Engineering)
The composite slab with steel trusses is composed of precast bottom plate and cast-in-place concrete. In engineering applications, cracks often appear in the bottom plate before casting the upper concrete, which even leads to the failure of the composite slab. To improve the crack resistance of the slab, a composite slab with additional steel trusses is proposed; that is, on the basis of the original longitudinal steel trusses, the transverse steel trusses are added. Static test and numerical analysis were carried out on the bottom plate of the new type of composite slab with the additional transverse steel trusses. The experimental and analytical results show that the load level of the plate with additional steel trusses can be increased by 33% under the normal service limit state; the deflection of the plate is significantly reduced and the crack development is effectively controlled, which illustrates that the new type of composite slab can improve the bearing capacity, increase the bending stiffness, and enhance the crack resistance effectively.